Activate Nyhamnen - Olsson, Haochun Xue (2014)

(untitled)
This thesis introduces Kongjian Yu’s design approach in terms of industrial heritage conservation in connection to transformation and urban design. The approach is examined respectively on two cases from China and USA. The thesis give a brief introduction to current achievement in conservation research and general profile of industrial conservation practice. Based on case and theory study, Yu’s design approach is carefully applied to an industrial area Nyhamnen in Malmö and a design proposal is produced. Study results shows that Yu’s design approach is an effective tool and it can be extensively applied as a framework to the design process. However, Yu’s approach has to be complemented by additional site investigations in order to be best implemented in practice.